VD_FINDINFO Décision / 2013 / 707 vom 27. Juni 2013 - VD Tribunal cantonal (2013)
RETRAITVOIE DE DROIT, FRAISEN GÉNÉRAL, DÉFENSE D'OFFICE, INDEMNITÉEN GÉNÉRAL | 135 al. 3 let. a CPP (CH), 386 al. 2 let. b CPP (CH), 428 al. 1 CPP (CH)